Customers’ attitude and purchase intention toward diminishing partnership home financing in Malaysia: a structural equation modeling approach - Abdul Razak, Dzuljastri; Abduh, Muhamad (2010)

(untitled)
Home financing in Malaysia is mainly focus on the debt-based Bai Bithaman Ajil (BBA) mode implemented for the first time in 1983. This concept is viewed by many scholars as similar to debt-based conventional home financing. As an alternative, the equity-based Musharakah Mutanaqisah or Diminishing Partnership (DP) financing was introduced in 2005. This study gauges customers’ perception on the salient features of DP home financing through a survey of 504 respondents comprise officers, managers and academician. Further analysis using the Structural Equation Modeling (SEM) was conducted to find out factors that influence customers’ intention for DP using the Theory of Reasoned Action (TRA) framework. The main findings indicated that customers perceived the equity sharing features in DP home financing mode differ from the conventional and BBA home financing modes. The analysis using SEM further indicates that customers’ intention for DP is influenced by their attitude and subjective norms.